2014
DOI: 10.7899/jce-14-18
|View full text |Cite
|
Sign up to set email alerts
|

Training and certification of doctors of chiropractic in delivering manual cervical traction forces: Results of a longitudinal observational study

Abstract: Objective: Doctors of chiropractic (DCs) use manual cervical distraction to treat patients with neck pain. Previous research demonstrates variability in traction forces generated by different DCs. This article reports on a training protocol and monthly certification process using bioengineering technology to standardize cervical traction force delivery among clinicians. Methods: This longitudinal observational study evaluated a training and certification process for DCs who provided force-based manual cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…3,6 Some work has been done to describe how loads differ when applied to various regions of the spine. 11 Efforts are now underway to use force feedback in training to help standardize the delivery of adjustments in clinical trials 12,13 and in education. Early chiropractic education, where students are taught first to deliver manual thrusts, has been revolutionized by the addition of force and speed feedback and training devices.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Some work has been done to describe how loads differ when applied to various regions of the spine. 11 Efforts are now underway to use force feedback in training to help standardize the delivery of adjustments in clinical trials 12,13 and in education. Early chiropractic education, where students are taught first to deliver manual thrusts, has been revolutionized by the addition of force and speed feedback and training devices.…”
Section: Introductionmentioning
confidence: 99%
“…24 Future studies may address this gap by assessing skill retention over time with additional instruction, such as instructor feedback, video feedback, a comparative reference for visual feedback, or modifying the number and frequency of practice thrusts and training sessions. Gudavalli et al [17][18][19] demonstrated that the recertification of ability to deliver prespecified forces using a low velocity manipulation may be necessary to maintain skill over time, which may generalize to HVLA-SM performance.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to deliver prescribed manipulative forces consistently also is necessary to address some questions related to treatment dosing, which can be answered only by applying standardized manipulative forces and loading rates. [17][18][19] Force-sensing technology has been used to train participants to deliver prescribed forces within wide ranges, 20 as a percentage of the clinician's maximum force, 21 and doubling or halving a clinician's typical force. 14 These training methods appear to decrease intraclinician variability, but they do not address the problem of inconsistent force delivery among clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Dosing was limited to three sets of five repetitions with contact over the C5 cervical vertebra and three sets of five repetitions with contact on the occiput. To insure inter- and intra-clinician proficiency in treatment implementation [ 46 ], we conducted pre-trial training sessions and monthly clinician recertification on traction force delivery using a process described elsewhere [ 43 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Based on the results of these preliminary studies, we concluded that developing a low-force minimal intervention will be a better choice than a sham treatment. We next developed a force feedback technology [ 42 ] to allow clinicians to deliver MCD within distinct traction force ranges, and tested a training and certification process using this technology [ 43 ]. These data led us to conclude that MCD could be delivered consistently within three different traction force ranges [ 44 ].…”
Section: Introductionmentioning
confidence: 99%